2021
DOI: 10.1002/advs.202101390
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the Interfacial Band Offset by the Molecular Dipole Orientation for a Molecular Heterojunction Selector

Abstract: Understanding and designing interfacial band alignment in a molecular heterojunction provides a foundation for realizing its desirable electronic functionality. In this study, a tailored molecular heterojunction selector is implemented by controlling its interfacial band offset between the molecular self‐assembled monolayer with opposite dipole orientations and the 2D semiconductor (1L‐MoS2 or 1L‐WSe2). The molecular dipole moment direction determines the direction of the band bending of the 2D semiconductors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…However, depolarization effect did not appear to be dominant in our study in which the transport properties showed a clear dipole dependence probably due to a low packing density of phenyl-based molecule SAMs. [59,60] Moreover, a series of recent studies [61,62] have reported a critical role of dipoles in the charge transport behaviors in large area molecular junctions, which supports that the depolarization effect can be neglected in these junctions. BPT has an intrinsic dipole moment, oriented from the thiol group (δ − ) to the molecular backbone (δ + ).…”
Section: Resultsmentioning
confidence: 92%
“…However, depolarization effect did not appear to be dominant in our study in which the transport properties showed a clear dipole dependence probably due to a low packing density of phenyl-based molecule SAMs. [59,60] Moreover, a series of recent studies [61,62] have reported a critical role of dipoles in the charge transport behaviors in large area molecular junctions, which supports that the depolarization effect can be neglected in these junctions. BPT has an intrinsic dipole moment, oriented from the thiol group (δ − ) to the molecular backbone (δ + ).…”
Section: Resultsmentioning
confidence: 92%
“…This result is also consistent with that of our previous report obtained using the conductive atomic force microscopy (CAFM) technique. [32] For example, in the WSe 2 /F6H2 heterojunction, because the valence band edge is located between the bias window at V = −1.0 V, the holes only feel the molecular tunnel barrier. Consequently, the transport current is enhanced.…”
Section: Resultsmentioning
confidence: 99%
“…Two-dimensional (2D) van der Waals semiconducting transition metal dichalcogenides (TMDs) can be considered promising candidates for nanoscale heterojunction unit that vertically connects to molecular SAMs. [31][32][33] They are ultrathin optoelectronic materials, exhibiting significantly higher light absorption per unit thickness than that by typical 3D semiconductors such as Si, GaAs, and even perovskites. [34][35][36][37] Moreover, owing to their intrinsically passivated surfaces devoid of dangling bonds, 2D TMDs result in high-quality heterostructures, in which traps do not hinder the charge transport across the interface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical role of the interface in CT across (bio)­molecular junctions has been long recognized ,, and includes three main contributions: (i) energy alignment, (ii) molecule–electrode coupling strength (Γ, in eV), and (iii) amount of available carriers. Energy alignment dictates the energy barrier (ε 0 , in eV) between the electrode’s Fermi level and the nearest molecular level, which, in turn, depends on the vacuum position of these levels and interfacial charge rearrangement upon formation of the contacts with the electrodes and associated interface dipoles. This interfacial charging can yield very similar ε 0 for a given (series of) molecule(s) despite large differences (even as large as 1.5 eV) in the electrode’s Fermi position .…”
Section: Introductionmentioning
confidence: 99%